COMPARATIVE ANALYSIS OF THE SPORTS-PEDAGOGICAL TRAINING SYSTEM FOR ATHLETES IN CHONGQING AND BISHKEK:USING THE EXAMPLE OF TENNIS - Huang, Dalin; Kanat, Dzhanuzakov; Gao, Zhibin; Zhao, Yongchao; Yu, Zhiyang (Veredas do Direito, 2026)
This study presents a comparative analysis of the sports-pedagogical training systems for tennis athletes in Chongqing (People’s Republic of China) and Bishkek (Kyrgyz Republic), conceptualizing the city as a meso-level unit of athlete development. Guided by a framework linking city-level systemic inputs to sports-pedagogical training processes and athlete development outcomes, the study adopts a qualitative comparative case study design based on document analysis. The findings indicate that Chongqing operates within a state-coordinated and vertically integrated training system characterized by dense development pathways, standardized coaching practices, and structured monitoring mechanisms. In contrast, Bishkek relies on a more decentralized, federation- and club-based system marked by greater variability in training processes, lower competition density, and limited institutional support. The comparison demonstrates that differences in governance arrangements and resource environments are closely associated with the coherence and sustainability of athlete development pathways. By focusing on the city as the unit of analysis and tennis as a representative sport, this study contributes to comparative sport pedagogy and provides empirical insights into how training systems function under contrasting institutional conditions.